Du vieux vin dans une outre neuve: Notes critiques à propos d'un nouveau dictionnaire sur Jésus - Piovanelli, Pierluigi (Revue de l'histoire des religions, 2022)
The Dictionnaire Jésus published under the auspices of the École Biblique et Archéologique Française de Jérusalem presents, alongside relevant articles, many entries that are problematic. The authors are in fact motivated by the apologetic desire to show the continuity that might exist between the historical Jesus and the Savior confessed by the Churches. This leads them to postulate gratuitously the early constitution of a stabilized memory and to multiply anachronisms. Such difficulty in restoring the historical dimension of religious phenomena raises the question of the scientificity of their undertaking.